Determination of noise equivalent quanta of medical screen-films - Wan Hassan, Wan Muhamad Saridan; Munajat, Yusof; Sahibuddin, Shamsul (Penerbit UTM Press, 2004)

(untitled)
Noise equivalent quanta (NEQ) of Lanex Regular/T Mat G and Lanex Regular/T Mat L screen-film combinations were determined using modulation transfer function (MTF) and noise power spectrum (NPS) data. To accomplish this, average gamma of the radiograph was computed, the MTF and the NPS data were linearly interpolated and these values were used to compute the NEQ by means of a computer program. The computation shows that for spatial frequency 0–0.7 cycles/mm the NEQ of Lanex Regular/T Mat G is slightly lower than that of Lanex Regular/T Mat L, for spatial frequency 0.7–1.5 cycles/mm the NEQ of both are almost the same, and for frequencies greater than 1.5 cycles/mm the NEQ of the former is greater than that of the latter. Relatively, this indicates that low frequency signals show better on Lanex Rregula/T Mat L, but high frequency signals show better on Lanex Regular/T Mat G.